Establishment of Hairy Root Cultures of Rhaponticum carthamoides (Willd.) Iljin for the Production of Biomass and Caffeic Acid Derivatives. (24th February 2015) - Skała, Ewa; Kicel, Agnieszka; Olszewska, Monika A.; Kiss, Anna K.; Wysokińska, Halina
Abstract : The aim of the study was to obtain transformed roots of Rhaponticum carthamoides and evaluate their phytochemical profile. Hairy roots were induced from leaf explants by the transformation of Agrobacterium rhizogenes strains A4 and ATCC 15834. The best response (43%) was achieved by infection with A4 strain. The effects of different liquid media (WPM, B5, SH) with full and half-strength concentrations of macro- and micronutrients on biomass accumulation of the best grown hairy root line (RC3) at two different lighting conditions (light or dark) were investigated. The highest biomass (93 g L −1 of the fresh weight after 35 days) was obtained in WPM medium under periodic light. UPLC-PDA-ESI-MS 3 and HPLC-PDA analyses of 80% aqueous methanol extracts from the obtained hairy roots revealed the presence of eleven caffeoylquinic acids and their derivatives and five flavonoid glycosides. The production of caffeoylquinic acids and their derivatives was elevated in hairy roots grown in the light. Only light-grown hairy roots demonstrated the capability for the biosynthesis of such flavonoid glycosides as quercetagetin, quercetin, luteolin, and patuletin hexosides. Chlorogenic acid, 3, 5-di- O -caffeoylquinic acid and a tentatively identified tricaffeoylquinic acid derivative were detected as the major compounds present in the transformed roots.